PENGEMBANGAN MEDIA PEMBELAJARAN KONEKSI (KARTU EDUKASI INTERAKTIF KODEWI) UNTUK MENINGKATKAN MOTIVASI SISWA KELAS VII - Siti Komala Dewi; Najib Jauhari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Interesting and interactive learning media is an important factor in increasing students motivation to learn in social studies subjects, especially material on socio-cultural diversity in society.The low motivation and lack of student involvement in the learning process prompted this research to develop an interactive learning media in the form of a domino card game called KONEKSI (Kodewi Interactive Education Cards). So far, social studies learning tends to use the lecture method so that students easily feel bored and less active participating in learning. Therefore, it is necessary to innovate learning media that can improve student learning so that they are encouraged to participate actively, show high enthusiasm, and be optimally involved in the learning process. This research aims to develop KONEKSI learning media to increase the learning motivation of seventh-grade students. This research uses the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. KONEKSI media was developed by applying the Game Based Learning (GBL) approach so that students can learn while playing through the activity of matching domino cards with questions and answers. The validation results show that this media is very suitable for use with a validation percentage of material experts of 94% and validation of media experts of 92%. The implementation of media in seventh grade students showed an increase in student learning motivation of 91% with a very high category. KONEKSI media is also able to create a more active, enjoyable, and interactive learning atmosphere so that students can learn. Further research is recommended to develop KONEKSI media in digital form to make it more flexible and easy to use in technology-based learning.